Trial by Jury as "Mockery of Justice": Party Contention, Courtroom Corruption, and the Ironic Judicial Legacy of Antimasonry. (26th January 2016) - Bussiere, Elizabeth
Abstract : Sweeping across the social and political landscape of the northeastern United States during the late 1820s and early 1830s, the Antimasonic Party has earned a modest immortality as the first "third" party in American history. In pamphlets, speeches, sermons, protests, and other venues, Antimasons lambasted the fraternal order of Freemasonry as undemocratic, inegalitarian, and un-Christian, reviling it as a threat to the moral order and civic health of the Early Republic. Because they believed that the fraternal organization largely controlled all levels of government, antebellum Antimasons first created a social movement and then an independent political party. Even before the full emergence of modern mass democratic politics, Antimasons demonstrated the benefits of party organization, open national nominating conventions, and party platforms. Scholars with otherwise different perspectives on the "party period" tend to agree that Antimasonry had an important impact on what became the first true mass party organizations—the Jacksonian Democrats and the Whigs—and helped push the political culture in a more egalitarian and populist direction.